Journeys beyond the neatline : - Rangel, Matthew (University of Alberta Libraries, 2010)
Showcases 25 pieces of cartographic artwork by Matthew Rangel and Michael Coulis. This title explores the connection between physical journeys and inner landscapes, place and personhood, geography and memory.